‘Caught in the act’; evidence for asteroid predation on plesiosaur (elasmosaurid) carcasses from the Upper Cretaceous of Hokkaido, Japan - Hunter, Aaron (2010)
We report the unusual occurrence of an asteroid preserved within the metapodials bones (flipper) of a plesiosaur from the Upper Yezo Group of Hobetsu, Hokkaido. Not only is this specimen one of the few asteroids reported from the Late Cretaceous, Japan, but it appears to be very well preserved with many of the marginal plates found intact. A number of long necked elasmosaurid (Plesiosauroidea) have been found across the Upper Coniacian to Campanian of northern and central Hokkaido, Japan. At Hobetsu Museum, the majority of elasmosaurid skeletons are found preserved in calcareous nodules within massive mudstones as semi-disarticulated post-cranial skeletons preserving just one part of the animal. Many examples show preserved limbs, paraxial section and the vertebral column. However, our example from only preserves the metapodials and phalanges (centre part of the flipper). These remains occur within lithofacies interpreted as continental slope, a deepwater substrate. (Obata, Matsukawa and Shibata, 2007) We suggest that, like many plesiosaur skeletons found in Hokkaido, either the limb became detached from the post-cranial skeleton shortly after death in early necrosis and sank to the seabed, or it became detached during the subsequent benthic activity. Nevertheless, after death the plesiosaur would have become a ‘fall’ community, similar to post-Cainozoic whale falls. The preserved semi-articulated asteroid appears to resemble the Late Cretaceous genus Recurvaster (Goniasteridea) found in the White Chalks of England and Denmark. Recurvaster are rarely preserved articulated; this is normally a result of exceptional preservation within soft sediments such as Chalks and is seldom seem in the more muddy sediments of Hobetsu, which preserve very few articulated multi-element taxa such as isocrinid crinoids. We suggest that this starfish was either feeding off the carcass or preying on neighbouring organisms within the nutrient rich benthic island community on the seabed. The asteroid itself was subsequently entombed, by rear influx soft sediment, with its marginal plates being held in place by the weakly disarticulated metapodials of the elasmosaurid; thus exceptionally preserving both organisms together within the same concretion.